Sensing capabilities of higher order cladding modes - Ioannou, Andreas; Theodosiou, Antreas; Kalli, Kyriacos; Caucheteur, Christophe (My University, 2018)
In this work, 5-mm long TFBGs were inscribed in photosensitive single-mode optical fiber using the direct writing plane-by-plane femtosecond laser inscription method; a flexible inscription approach that enables absolute control of the grating period, length, angle, width and depth of the grating planes. This new fabrication method brings important differences compared to classical inscription methods. Firstly, these gratings exhibit very low photo-induced birefringence (measured ∼8pm) and as we rely on a direct writing process, the tilt angle of the inscribed grating does not affect the Bragg wavelength, allowing for precise positioning. In addition, this method enables the high order grating production, allowing a behavioral study of higher order cladding modes located at lower wavelengths in the 1200-1600 nm range. 8th order gratings were produced with cladding and Bragg mode resonances in the C+L bands. The temperature and strain sensitivities were measured for both the Bragg and higher order cladding modes, yielding an exceptional performance. The higher order modes exhibit a negative axial strain, up to-1.99nm (more than two times higher than the standard Bragg peaks) and a solid temperature sensitivity of 10.25 pm/°C: At the same time, for the designed order cladding modes (of the 8th) the refractive index sensitivity is measured at 22 nm/RIU.
Keywords: Femtosecond; Higher order cladding modes; Optical fiber sensors; Tilted fiber Bragg gratings